Smoke visualization of free-flying bumblebees indicates independent leading-edge vortices on each wing pair - Bomphrey, R; Taylor, G; Thomas, A (2009)
It has been known for a century that quasi-steady attached flows are insufficient to explain aerodynamic force production in bumblebees and many other insects. Most recent studies of the unsteady, separated-flow aerodynamics of insect flight have used physical, analytical or numerical modeling based upon simplified kinematic data treating the wing as a flat plate. However, despite the importance of validating such models against living subjects, few good data are available on what real insects actually do aerodynamically in free flight. Here we apply classical smoke line visualization techniques to analyze the aerodynamic mechanisms of free-flying bumblebees hovering, maneuvering and flying slowly along a windtunnel (advance ratio: -0.2 to 0.2). We find that bumblebees, in common with most other insects, exploit a leading-edge vortex. However, in contrast to most other insects studied to date, bumblebees shed both tip and root vortices, with no evidence for any flow structures linking left and right wings or their near-wakes. These flow topologies will be less efficient than those in which left and right wings are aerodynamically linked and shed only tip vortices. While these topologies might simply result from biological constraint, it is also possible that they might have been specifically evolved to enhance control by allowing left and right wings to operate substantially independently. © 2009 Springer-Verlag.